Adoption of recommended cultivation practices in ginger (Zingiber officinale Rosc.) at Koraput District, Orissa - P Acharya, S C Mohapatra, (Journal of Spices and Aromatic Crops, 2006)
A study was conducted in Koraput District (Orissa) for determining the level of adoptionand constraints in adoption of recommended cultivation techniques in ginger (Zingiberofficinale) among farmers. The overall adoption level of improved cultivation techniques waslow (44.1%) and the major constraints in their adoption was lack of technical guidance(39%), ignorance (38.4%) and high cost of inputs (36.2%).